Perancangan Distributed Generation Menggunakan Phasor Measurement Unit - Saputra, Rangga Eka; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The aim of this research is to design a Distributed Generation (DG) connected system with solar cell source using Matlab/Simulink R2016a, build a Phasor Measurement Unit (PMU) connected to DG using Matlab/Simulink R2016a, operate a DG system connected to solar cell for monitoring voltage and phasor currents through PMU. This research was conducted using simulations found in the Matlab R2016a application where the system consists of 4 buses, 2 loads with a voltage of 20 kV, 2 voltage boosters, 20 kV, and 4 transmission lines. The results showed that the impact of the DG system using this PMU has improved the quality of the power generated from both sources, namely the 150-kV network and the DG supplied at both loads. In addition, the results of this data prove that DG has a role in maintaining power at a stable load and increasing energy efficiency by reducing power losses in this DG connected system. The DG connected to the system has an effect on increasing the current in each bus, so that the load current has increased from before, giving an effect on increasing the voltage in each bus, so that the voltage on both loads has increased from before. This comparison also shows the results of the positive sequence value of phasor currents and phasor voltages before and after DG Keywords: Distributed Generation, Phasor Measurement Unit, solar cell